PELAKSANAAN TANGGUNG JAWAB SOSIAL PT. RIGUNAS AGRI UTAMA DALAM RANGKA PENINGKATAN MUTU PENDIDIKAN MASYARAKAT DI KECAMATAN PERANAP KABUPATEN INDRAGIRI HULU - Nadia Fadiah Zendrato; Firdaus Firdaus; Setia Putra (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2022)
The implementation of corporate social responsibility is an obligation that must be carriedout by a company in carrying out its corporate activities. This is explicitly regulated in Article 47 ofLaw Number 40 of 2007 concerning Limited Liability Companies. This obligation is alsoreaffirmed geographically in the Regional Regulation of Riau Province Number 6 of 2012concerning Corporate Social Responsibility in Riau Province. PT Rigunas Agri Utama is acompany engaged in the plantation and processing of palm oil refineries. Located in Peranap sub-district, Indragiri Hulu Regency, PT Rigunas Agri Utama has been running CSR programs in theeducation sector through schools in the surrounding area. As for the legal issues are about variouskinds of CSR implementation efforts and the obstacles that often occur. The essence of theimplementation of CSR is not only in the presence or absence of CSR, but the continuity of theimplementation of CSR which continues to be carried out, especially in the field of education inorder to increase the nation's intelligence and improve the existence of the company. Therefore,this research departed on the basis of a desire to oversee every CSR implementation in theeducation sector by PT Rigunas Agri Utama. This is done, so that the CSR program is not carriedout as a mere formality without any improvement in the quality of the education sector. Especiallyin several schools in the surrounding area that still need assistance from the CSR program.This research is a sociological juridical legal research, namely a research approach thatemphasizes the legal aspects (laws and regulations) regarding the subject matter to be discussed,associated with the reality in the field. This study uses primary data sources consisting of primary,secondary, and tertiary legal materials.From the results of the research and discussion conducted, there are several conclusionsobtained, namely: First, the existence of CSR as a mandatory program for companies in the form ofPT Rigunas Agri Utama in Peranap sub-district has not been implemented properly. Weak intensityand continuity of CSR program implementation tend not to be implemented even temporarily. Thenormativity of CSR which should be used as a basic guideline that departs from the values of legalcompliance should make CSR a superior program that must be carried out regularly. Theimplementation of CSR in the field of education is also an embodiment of the company's role insupporting intelligence for the community as a state goal. Second, there are several obstacles inimplementing the CSR program, such as the COVID-19 pandemic and the lack of coordinationbetween the school and the PT Rigunas Agri Utama Company. Therefore, it is necessary to plan,implement and supervise the implementation of CSR well. Improved coordination is also neededfor the smooth distribution of CSR assistance such as infrastructure improvements, procurement ofsocial/volunteer activities, and also the provision of scholarships for outstanding andunderprivileged students.Keywords: CSR - Education – Legal Corporate